PERANCANGAN SISTEM ANALISIS KARAKTER SISWA-SISWI SMAN 79 JAKARTA BERBASIS JAVA - Septian Pratama; Agung Ferdinan Sandy; Aulia Ar Rakhman Awaludin (Jurnal Publikasi Teknik Informatika, 2022)
In conducting the character test of the students, SMAN 79 Jakarta uses the FSQ Personalitree concept which is still done manually. FSQ Personalitree is a personality character analysis test through the existing structure in the tree includes roots, fruits, branches and leaves. This character analysis system is designed to assist the school in conducting character tests so that it can determine the character of the students taking the test and present the processing of participant data and examiner data quickly and accurately accordance with the needs. The research method used in design this character analysis system is grounded research and carry out data collection methods with literature study methods, observations and interviews. After the author conducted the grounded research method, then the writer can draw the conclusion that there is a need for a character analysis system for SMAN 79 Jakarta students that can provide information on the results of character analysis and is stored properly in the system database. So that it can be accessed easily by guidance and counseling teachers, SMAN 79 Jakarta. This character analysis system was successfully implemented to be application used Java programming language and MySQL database.